The Glucan-Remodeling Enzyme Phr1p and the Chitin Synthase Chs1p Cooperate to Maintain Proper Nuclear Segregation and Cell Integrity in Candida albicans - Degani, Genny; Popolo, Laura (Frontiers in Cellular and Infection Microbiology, 2019)
GH72 family of -(1,3)-glucanosyltransferases is unique to fungi and is required for cell wall biogenesis, morphogenesis and virulence, and in some species is essential for life. Candida albicans PHR1 and PHR2 are pH-regulated genes that encode GH72 enzymes highly similar to Gas1p of Saccharomyces cerevisiae. PHR1 is expressed at pH ≥ 5.5 while PHR2 is transcribed at pH ≤ 5.5. Both are essential for C. albicans morphogenesis and virulence. During growth at neutral-alkaline pH, Phr1p-GFP preferentially localizes to sites of active cell wall formation as the incipient bud, the mother-daughter neck, the bud periphery and concentrates in the septum at cytokinesis. We further investigated this latter localization. In chs3 cells, lacking the chitin of the chitin ring and lateral cell wall, Phr1p-GFP still concentrated along the thin line of the primary septum formed by chitin deposited by chitin synthase I (whose catalytic subunit is Chs1p) suggesting that it plays a role during formation of the secondary septa. RO-09-3143, a highly specific inhibitor of Chs1p activity, inhibits septum formation and blocks cell division. However, alternative septa are produced and are crucial for cell survival. Phr1p-GFP is excluded from such aberrant septa. Finally, we determined the effects of RO-09-3143 in cells lacking Phr1p. PHR1 null mutant was more susceptible to the drug than the wild type. The phr1 cells were larger, devoid of septa and underwent endomitosis and cell death. Phr1p and Chs1p cooperate in maintaining cell integrity and in coupling morphogenesis with nuclear division in C. albicans.